(untitled) (Strathmore Law Journal, 2020)
Kenyan superior courts missed an opportunity to discuss and authoritatively settle the law on the nature of copyright in broadcasts and the effect of the must carry rule in digital broadcasting through their decisions in the Royal Media Services case. The Supreme Court, in arriving at its decision, failed to be guided by Kenyan law on copyright in broadcasts and the must carry rule in three key areas. First, the Supreme Court relied on the Philippines’ decision on the definition of a broadcasting organisation without considering the provisions of the Copyright Act (Chapter 130) and the Kenya Information and Communication Act (Chapter 411). Second, the Supreme Court relied on the doctrine of fair use as envisaged in the Philippines copyright regime, yet Section 26 of the Kenyan Copyright Act provides for fair dealing. Third, the Supreme Court relied on the public interest defence without discussing its basis and establishing its parameters, especially since public interest is not provided for in Copyright Act. The Supreme Court erred in determining that rebroadcasting of local broadcasts by subscription television licencees was not an infringement of copyright in broadcast.